2020
DOI: 10.1029/2019wr025330
|View full text |Cite
|
Sign up to set email alerts
|

Water Governance Contribution to Water and Sanitation Access Equality in Developing Countries

Abstract: Access to basic water service and basic sanitation service has been acknowledged as fundamental human rights. It also has been mentioned in UN Sustainable Development Goals 6 to ensure that all people will have equal access to both water and sanitation service, as well as embedded in Goal 10 that aims to reduce inequality and promoting inclusiveness. However, the WHO/UNICEF Joint Monitoring Programme 2017 reported that 844 million people are still living without basic access to water, and 2.3 billion are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 54 publications
(49 reference statements)
0
32
0
4
Order By: Relevance
“…In view of this exploration, the results in (El Khanji 2018 ) suggest that aid is targeting urban areas while there is a clear evidence that care should be taken for the rural areas, and most of the aid is not targeting places that are really in need. Bayu et al ( 2020 ) found that the inequality in safe access to water and sanitation is driven by different social, political (government effectiveness) and economic aspects (absorption of aid funds) of water governance in the developing countries. Therefore, donors’ motivations, whether they are strategic, economic or political, beat the efficiency of aid and mislead the efficient allocation of aid for different subsectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In view of this exploration, the results in (El Khanji 2018 ) suggest that aid is targeting urban areas while there is a clear evidence that care should be taken for the rural areas, and most of the aid is not targeting places that are really in need. Bayu et al ( 2020 ) found that the inequality in safe access to water and sanitation is driven by different social, political (government effectiveness) and economic aspects (absorption of aid funds) of water governance in the developing countries. Therefore, donors’ motivations, whether they are strategic, economic or political, beat the efficiency of aid and mislead the efficient allocation of aid for different subsectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The provision of and access to basic water and sanitation services has been recognized as a fundamental right to human survival (Bayu, Kim, & Oki, 2020;Sogbanmu, Aitsegame, Otubanjo, & Odiyo, 2020). According to research conducted by the United Nations (2020) one in three people in the world do not have access to safe drinking water and three in ten do not have access to safely managed drinking water services.…”
Section: Sdg 6 (Clean Water and Sanitation) And Sdg 7 (Affordable And Clean Energy)mentioning
confidence: 99%
“…Water is an important liquid for human beings, the universe, and all life existing on earth [ 1 , 2 ]. This liquid can be easily polluted by different dyes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%